Enhancing Students’ Listening Motivation in Hikayat Texts through Culturally Responsive Teaching in Senior High School - Purnawan, Lalu Dedi; Sari, Rini Kurniatun; Usman, Usman; Al-Pansori, Muh. Jaelani (Sean Institute, 2026)
Listening instruction on hikayat texts in senior high schools often encounters low student learning motivation due to instructional practices that lack contextual relevance and insufficient integration of students’ cultural backgrounds. This study aims to enhance students’ learning motivation in listening to hikayat texts through the implementation of the Culturally Responsive Teaching (CRT) approach. The research employed a collaborative classroom action research design using a lesson study framework consisting of the stages of plan, do, and see. The study was conducted in class X-1 of SMA Negeri 2 Praya and involved 36 students. The research was carried out in two cycles. Data were collected through learning motivation questionnaires, cognitive achievement tests, classroom observations, and reflective documentation. Data analysis was conducted using descriptive quantitative and qualitative methods. The findings reveal a significant improvement in students’ learning motivation following the implementation of CRT. In the pre-action phase, students’ motivation was predominantly categorized as low to moderate. After the implementation of CRT in Cycle I and Cycle II, the proportion of students with high learning motivation increased substantially, reaching 72% in Cycle II, while no students remained in the low-motivation category. These results indicate that the CRT approach is effective in fostering culturally relevant, meaningful, and engaging listening instruction for hikayat texts at the senior high school level.